A STUDY ON NEO-BANKING IN INDIA: GROWTH, CHALLENGES, AND FUTURE PROSPECTS - Kailashbhai, Raut Nileshkumar (International Journal of Research -GRANTHAALAYAH, 2025)
Offering creative, user-friendly, and technology-driven banking solutions, neobanks—also known as digital-only banks—are transforming the Indian financial system. Unlike conventional banks with actual locations, neobanks run entirely online using cutting-edge technology to provide smooth financial solutions. The rise of neobanks in India, their operating models, major services, and obstacles they encounter in a quickly changing market are discussed in this research paper. It also looks at the future possibilities of neobanks, underlining their capacity to revolutionize the banking scene while tackling regulatory, technological, and competitive obstacles. By means of a thorough review of literature, corporate reports, and market research, this study hopes to present a clear picture of neo banking in India, its effects on the financial sector, and its part in determining the future of banking.